An Investigation of the Theory Practice Gap in Professional Sales. Issue 1 (2nd January 2017) - Pullins, Ellen Bolman; Timonen, Hanna; Kaski, Timo; Holopainen, Mari
Abstract : This article considers the theory-practice gap in professional sales. Scholars note a discrepancy between scholarly knowledge and the practice of selling. We study three exemplar gaps using an extensive qualitative dataset, mainly in-depth interviews, in order to better understand why these gaps exist. Theory-practice gaps in listening, follow-up, and adaptability have not been empirically confirmed in light of rapid change in the sales field. After confirming these gaps, we explore antecedents, uncovering several underlying reasons for gap formation. We consider theoretical and managerial implications. In particular, we elaborate on the need for theory to be more relevant and contextualized.